Cannabis Use Among Remote Indigenous Australians: Opportunities to Support Change Identified in Two Waves of Sampling - Graham, Veronica E.; Clough, Alan R. (Frontiers in Public Health, 2018)
Background: Cannabis harms among Indigenous populations in Australia, New Zealand, Canada and the United States may be magnified by poorer health and heavy use. However, little direct evidence is available to evaluate cannabis' impacts. In communities in remote northern Queensland (Australia) where cannabis has become endemic, opportunities to support change were investigated. Methods: Opportunistically recruited participants (aged 15–49 years) discussed their cannabis use history in interviews in two waves of population sampling in Cape York (Queensland). Wave 1 included 429 people (235 males and 194 females); and wave 2 included 402 people (228 males and 174 females). Current users (used cannabis during the year before interview) described frequency of use, amount consumed, expenditure and dependence symptoms. Other substance use was recorded for 402 people at wave 2. Results: Wave 1: 69% reported lifetime use and 44% current use. Males (55%) were more likely than females (30%) to be current users (P < 0.001). Most (96%) current users described at least weekly use; nearly half (48%) were “heavy” users (≥6 cones/session at least once/week) and 77% met cannabis dependence criteria. Three communities spent up to AUD14,200/week on cannabis, around AUD2.0 million/year, or around 9% of community people's total income on cannabis. The majority (79%) of current users wanted to quit or reduce their cannabis use. Wave 2: no difference was observed in the proportion of lifetime (69%, |z| = 0.04, P = 0.968) or current cannabis users (39%, |z| = 1.39, P = 0.164); nor current use among males (71%, |z| = 0.91, P = 0.363) or females (62%, |z| = 0.36, P = 0.719). However, a significant reduction in current users by 15% (|z| = 2.36, P = 0.018) was observed in one community. Of 105 wave 1 current users re-assessed in 2, 29 (27%) had ceased use. These participants reported cost and family commitments as reasons to change and that social support and employment enabled abstinence. Current and lifetime cannabis use were closely associated with all other substance use, particularly tobacco and alcohol (both P > 0.001). Conclusions: High rates of heavy cannabis use in remote Australian Indigenous communities warrant action. Successful cessation among some individuals suggests that significant opportunities are available to support change even where cannabis use may be endemic.